2001
DOI: 10.1097/00126334-200101010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Heterogeneous Adherence to HIV-Antiretroviral Therapies in the Multicenter AIDS Cohort Study

Abstract: Assessment of adherence to HIV antiretroviral therapy (ART) is required for studying therapeutic effectiveness and identifying subgroups needing focused education. The study's goals were to describe the level of ART adherence using self-reported recall over a 4-day period and to characterize determinants of lower adherence. The interaction between adherence and drug holidays on level of HIV RNA also was investigated. Perfect self-reported adherence was defined as taking all doses and numbers of pills as prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
118
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(128 citation statements)
references
References 37 publications
6
118
4
Order By: Relevance
“…While the low number of patients reporting suboptimal adherence to dose instructions was similar to rates reported in other studies (Cederfjä ll, 2002;Jensen-Fangel et al, 2002;Kleeberger et al, 2001;Molassiotis et al, 2002;Walsh, Horne, & Dalton, 2001), suboptimal adherence rates to schedule and dietary instructions were higher in our sample than those reported by Murphy et al (2004). Patients quite often express that their medication controls their lives and the difficulty of integrating medications into their daily activities as a major reason of suboptimal adherence (Ammassari et al, 2001;Chesney et al, 2000;Gifford et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…While the low number of patients reporting suboptimal adherence to dose instructions was similar to rates reported in other studies (Cederfjä ll, 2002;Jensen-Fangel et al, 2002;Kleeberger et al, 2001;Molassiotis et al, 2002;Walsh, Horne, & Dalton, 2001), suboptimal adherence rates to schedule and dietary instructions were higher in our sample than those reported by Murphy et al (2004). Patients quite often express that their medication controls their lives and the difficulty of integrating medications into their daily activities as a major reason of suboptimal adherence (Ammassari et al, 2001;Chesney et al, 2000;Gifford et al, 2000).…”
Section: Discussionsupporting
confidence: 86%
“…Patients who receive a protease inhibitor (PI)-based medication regimen are more likely to report lower levels of adherence to dose than those receiving nonnucleoside reverse transcriptase inhibitors (NNRTI) regimens (Altice, Mostashari, & Friedland, 2001;Kleeberger et al, 2001;Mannheimer, Friedland, Matts, Child, & Chesney, 2002). Other studies have shown that adverse side effects are strongly associated with suboptimal adherence to dose instructions (Ammassari et al, 2001;Bartlett, 2002;Catz, Kelly, Bogart, Benotsch, & McAuliffe, 2000;Duran et al, 2001;Gao, Nau, Rosenbluth, Scott, & Woodward, 2000;Gifford et al, 2000;Molassiotis et al, 2002;Murphy, Marelich, Hoffman, & Steers, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a recall period of at least 7 days insures that a weekend, which is often associated with adherence difficulties, will be included (Simoni et al, 2006). Accordingly, two different recall periods were used for self-reported adherence (Kleeberger et al, 2001;Murphy et al, 2004). The total number of missed doses in the past 4 days and past 2 weeks, in conjunction with the total number of possible doses during the past 4 days and past 2 weeks, were used to yield both 4-day and 2-week percent self-reported adherence scores.…”
Section: Self-report Measure Of Antiretroviral Medication Adherencementioning
confidence: 99%
“…A number of studies have supported the relationship between depressive symptoms and treatment nonadherence among heterogeneous samples of HIVpositive men (Catz et al 2000;Gonzalez et al 2004;Gordillo et al 1999;Hirschhorn et al 1998;Kleeberger et al 2001;Paterson et al 2000;Safren et al 2001;Simoni et al 2002). Symptoms of depression make the already difficult task of adhering to HIV treatment regimens much more difficult for patients.…”
Section: Depression and Hiv-positive Latinosmentioning
confidence: 99%